Osteoporosis-Concerned Group and Empowering Elderly Model to Increase Calcium Intake: a Study Among Indonesian Elderly - Saryono, Saryono; Nani, Desiyani; Proverawati, Atikah; Hidayat, Arif Imam (Jurnal Keperawatan Soedirman, 2018)
Aging process leads to decline in body functions, including in musculoskeletal system. Bone mass loss (osteoporosis) is one of the problems in musculoskeletal system which often experienced by elderly. Osteoporosis could have a great impact on elderlys life, such as increased risk of fractures and decreased quality of life. The objective was to construct models of the formation of osteoporosis care group (OCG) and empowerment of the elderly to increase calcium intake to reduce the osteoporosis incidence. This study uses Participatory Rural Appraisal (PRA) approach. Participants are Posyandu Lansia cadresand members of Posyandu Lansia in the Dawuhan village, Padamara District, Central Java, Indonesia. The following steps were implemented in this study 1) problem identification 2) formation of OCG, 3) OCG training, and 4) OCG mentoring process. Data was analyzed using qualitative method. Results showed that knowledge and skills of OCG members in regards to osteoporosis management were improved following training andmentoring process. Further, OCG members can apply their knowledge and skills toempower elderly for increasing calcium intake. OCG which is involving cadres and community leaders and elderly as its members are very important to cultivate awareness in health maintaining in order to prevent osteoporosis.